CIRCULATING TUMOUR ASSOCIATED ANTIGENS AS AID TO EARLY DIAGNQSIS OF CARCINOMA OF CERVIX (1982)
Earlier studies by this author in 1976 provided evidence of an association between an infective, sexually transmitted agent, the Herpes Simplex Virus Type-2 (HSV—2) and human carcinoma of the cervix, irrespective of geographic location or ethnic origin of the individuals. Similarly, HSV-2 related antigens were demonstrated by the indirect immuno-fluorescent technique in desquamated cells of carcinoma of the cervix tissues from tumour bearing patients. To highlight the Potentials of the detection of tumour antigens in tumour-faearing patients as aid to early diagnosis of the cancer, Isolation and purification of the Tumour Associated Antigens (TAA) of human cancer of the cervix were attempted by immunological and physicochemical procedures in this study. Two antigen preparations, one the Soluble Antigens (SA), and the other, the Membrane Bound Antigens (MBA) were prepared from a pool of cancer of the cervix (CaCx) tissues. The soluble antigens were extracted by homogenization in Earle’s Balanced Salt Solution (EBSS) containing antibiotics, and the membrane-bound antigens were solublised by 3-molar potassiurn Chloride (3 Molar KCl). For isolation and purification of TAA, procedures for the purification of proteins were explored. These include physicochemical stepwise ammonium sulphate fractionation, sephadex ion exchange chromatography, sephacryl S-200 gel filtration, and affinity chromatography to eliminate the normal tissue components of the antigen fractions. Hyperimmune rabbit sera were then prepared against the partially purified TAA. Immunodiffusion studies, employing hyperimmune rabbit sera prepared against the partially purified TAA were used to demonstrate tumour associated antigens in the various cancer antigen preparations, and Circulating Tumour Associated Antigens (C-TAA) in the sera of tumour- bearing patients. The TAA in the cancer tissues showed lines of identity with the C-TAA in patients sera. Techniques involving adsorption by immuno-precipitation-in-gel with Normal Cervix (NCx) tissue antigen preparations, and pooled Normal Human Sera (NHuS) were utilized for the removal of antibodies to NCx and NHuS in the rabbit sera, after which there were no reactions with NCx indicating the specificity of TAA for CaCx. A comparison of the soluble and 3 Molar KCl extracts of the cancer antigens by immuno-precipitation reaction, using adsorbed hyperimmune rabbit sera prepared against the partially purified CaCx TAA, demonstrated three TAA (TAA-1, close to the central antisera well, TAA-2, intermediate and TAA-3, close to and curving towards the peripheral antigen well) in the soluble antigen preparation. Only one TAA (probably identical to the TAA-3 of the soluble antigen) was demonstrated in the 3 Molar KCl extract. Using the rabbit antisera against the partially purified CaCx TAA, adsorbed with NCx and NHuS, results of coded sera showed that immunodiffusion reaction was able to detect circulating TAA in 75.0 per cent of patients with cancer as compared with 5.6% in women with benign gynecological diseases, 1.4% in pregnant women and 0.0% in healthy control women. The result indicates that the test has great potential for immunodiagnosis of cancer of cervix. Although the sensitivity of the test method was low, the specificity was high, and could provide a means of early diagnosis of neoplastic changes in the cervix. The detection of Circulating-TAA as tumour markers in sera of patients, may someday become routine, and thus make earlier diagnosis of cancer possible. Indications are that immuno-diagnostic procedures can be designed in ways that are reproducible, simple and reliable. Such serological tests would extend our present ability for detection and monitoring of malignancies.